NO reduction with CO on alumina-modified silica-supported palladium and molybdenum-palladium catalysts - Díaz Cónsul, Julia María (2008)
In this work, Pd and Mo-Pd catalysts supported on Al2O3 modified SiO2 and Si-MCM-41 materials were prepared, characterized by H2 chemisorption and FTIR spectroscopy of adsorbed CO and NO and tested for the reduction of NO with CO. The characterization results indicated that in the bimetallic catalysts, Mo that is loaded first, migrates over the Pd atoms and reduced the fraction of exposed metal atoms. The reduction of NO with CO at 523 K showed that the specific activity for NO conversion increased as a result of the Pd-Mo interaction. In the 523–573 K temperature range NH3 was produced in addition to CO2, N2 and N2O. This result suggests the reaction of NCO species formed on the Pd surface with OH groups of the support materials to produce isocyanic acid (HNCO) that is hydrolyzed to NH3. The catalysts exhibited a decreasing selectivity to N2O and a parallel increase in the production of N2 and NH3 as the conversion increases. The effect of Mo on the reaction selectivity was clear for Pd/Al2O3/SiO2; at similar NO conversion level the selectivity to N2O and N2 decreased with increasing NH3 formation. FTIR spectra of adsorbed species under reaction conditions demonstrated the absence of isocyanate species and the presence of NH4 + ions in accordance with the high Brønsted acidity of the support materials.